2017
DOI: 10.22456/1982-8918.66851
|View full text |Cite
|
Sign up to set email alerts
|

Physical Education Classes and Inclusion of Children With Disability: Brazilian Teachers’ Perspectives

Abstract: This study analyzed Physical Education teachers' concept of inclusion and determined positive and negative aspects of inclusion in their classes. Interviews were conducted with 18 Physical Education teachers working in Brazilian public schools. Data collected were examined by content analysis to search for emerging themes. The findings showed that inclusion was understood as participation and learning for all children rather than only for those with disabilities. Team sports were pointed as the main challenge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 16 publications
(29 reference statements)
0
4
0
3
Order By: Relevance
“…In this regard, Hypothesis 3b can be accepted due to younger teachers reporting greater knowledge about the use of ICT with people with disabilities when compared with the older teachers. Previous research had already confirmed these finding [29]. One possible explanation to these results suggests that the young teachers have recently completed their teacher training and they began to incorporate these contents in their formative curriculum.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…In this regard, Hypothesis 3b can be accepted due to younger teachers reporting greater knowledge about the use of ICT with people with disabilities when compared with the older teachers. Previous research had already confirmed these finding [29]. One possible explanation to these results suggests that the young teachers have recently completed their teacher training and they began to incorporate these contents in their formative curriculum.…”
Section: Discussionmentioning
confidence: 59%
“…This is in line with previous research conducted in the international context such as those mentioned above [16][17][18][19], where this low level of training is also evident. These deficiencies in the teaching competence seem to be modulated by factors such as the gender [27,28] or even the age of the teachers, which seems to determine their level of competence in this field [29,30]. The years of teaching experience are also revealed as a determining factor in the level of ICTs skills, where teachers with less teaching experience tend to show a higher level of competence for the incorporation of ICTs [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…This may reflect their awareness of the challenges and complexity associated with adapting in a real-world gym class with 20-30 children. In fact, some of the qualitative data highlighted the challenge of incorporating children with diverse needs into games, and this has been highlighted in other studies in Canada and around the world [50][51][52][53]. Conversely, it may also suggest that 5 h was not enough of an intervention dose or that JEPD needed to be enhanced in some way to achieve this outcome (e.g., in situ mentoring).…”
Section: Discussionmentioning
confidence: 98%
“…Sobre el neoliberalismo, éste es comprendido como una racionalidad económica que guía las acciones de la educación (Moreno Obando & Peña Ochoa, 2020), enfocando el quehacer educativo en el logro académico (Navarro-Aburto et al, 2016), para lo cual promueve la estandarización de las prácticas docentes sin considerar las diversas culturas y necesidades de estudiantes e instituciones educativas (Andrade & Freitas, 2016;Vasconcellos et al, 2016). Esta racionalidad conlleva a la construcción de políticas que no favorecen los procesos de inclusión (Alves et al, 2017;Lopes et al, 2016), particularmente porque son poco territoriales (Vásquez & Alarcón, 2016), comprenden la inclusión desde un modelo biomédico, se centran en el diagnóstico y en el trabajo de especialistas (Urbina Hurtado et al, 2017); y se orientan a casos puntuales y situaciones concretas, principalmente lo que definen como "condiciones de vulnerabilidad" (Navarro-Montaño, 2017).…”
Section: ¿Qué Barreras Para Avanzar En Inclusión Se Mencionan En Los ...unclassified
“…Para ello, las escuelas no deben centrarse en el ingreso de estudiantes con NEE, sino en asegurar la permanencia de estos (Delgado-Sanoja & Blanco-Gómez, 2016;Hernández Sánchez & Ainscow, 2020). Para ello, es fundamental que las instituciones educativas posean una definición clara sobre inclusión, explicita y con lineamientos precisos (Alves et al, 2017;Fernández-Fernández et al, 2016), tarea que requiere de la gestión de los equipos directivos (Alarcón-Leiva et al, 2020) para generar conciencia de la importancia de la diversidad (Escarbajal-Frutos et al, 2020). A su vez, se debe poner acento en las metodologías para la inclusión, para lo cual se propone: primero, un cambio de metodologías a nivel universitario, que prepare a los docentes en formación para los desafíos de la inclusión y la diversidad (Moriña, & Carballo, 2020;Balongo González & Mérida Serrano, 2017).…”
Section: ¿Qué Desafíos Existen Para Avanzar En Inclusión Según Las Pu...unclassified